Psychosocial Distress in Chronic Disease Patients in Salatiga - Muninggar, Jodelin - (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Patients of hypertension (HT), diabetes mellitus (DM) and mixed (DM-HT) have vulnerability to stress due to illness and psychosocial responses. The aim of research was to identify psychosocial distress, components and their relationship to levels of GDP, cystole/diastole and cholesterol on three groups. Quantitative survey research design for 42 people, with purposive sampling at the Manunggal Clinic. Taking psychosocial distress data with a standard questionnaire, while systole/diastole, GDP and cholesterol levels with examination in the laboratory, in April-May 2018. Analysis with Anova and Pearson test, ÃŽÂ±<0.05. Shows sufferers have low distress, moderate distress and high distress. Average score of emotional component (3.2), chronic disease management difficulties (3.2), difficulties with doctors (3.0) and difficulties with friends/people around (2.6). Anova test showed no significant difference in psychosocial distress scores (p=0,079). The Pearson test showed a weak correlation between psychosocial distress and systole; diastole; GDP and cholesterol. Conclusion: Psychosocial distress of chronic disease sufferers in Salatiga is included in the category of moderate and high distress, with the highest score on the emotional burden component and the difficulty of chronic disease management. There were no significant differences in psychosocial distress scores, blood pressure, blood sugar levels and cholesterol in the three groups.Ã‚Â